2017
DOI: 10.1111/bdi.12505
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐year progression of body mass index in a county‐wide cohort of people with schizophrenia and bipolar disorder identified at their first episode of psychosis

Abstract: Objective There is increased prevalence of obesity in schizophrenia and bipolar disorder, leading to disproportionate risk of adverse health conditions. Prospective, long-term weight gain data, however, are scarce. Methods We analyzed data from the Suffolk County Mental Health Project cohort of consecutive first admissions with psychosis recruited from September 1989 to December 1995 and subsequently followed for 20 years, focusing on people with schizophrenia (n=146) and bipolar disorder (n=87). The time co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 52 publications
2
38
0
1
Order By: Relevance
“…In analyses of data from the Suffolk County Mental Health Project, we examined the 20‐year course of weight gain and its impact on everyday functioning at the 20‐year follow‐up. We found that weight gain was progressive over the entire period, leading to over 50% of bipolar patients and 60% of schizophrenia patients having a body mass index in the obese range 20 years after diagnosis, a striking change from 8% and 20%, respectively, at the time of first diagnosis.…”
mentioning
confidence: 79%
“…In analyses of data from the Suffolk County Mental Health Project, we examined the 20‐year course of weight gain and its impact on everyday functioning at the 20‐year follow‐up. We found that weight gain was progressive over the entire period, leading to over 50% of bipolar patients and 60% of schizophrenia patients having a body mass index in the obese range 20 years after diagnosis, a striking change from 8% and 20%, respectively, at the time of first diagnosis.…”
mentioning
confidence: 79%
“…Consistent with this, after adjusting for symptom level, functioning level and use of antipsychotics with adverse metabolic side effects, several differences in CVD risk factors between the diagnostic groups disappeared, while obesity, waist, LDL‐C and diastolic BP remained significantly higher in the SCZ group. Some recent studies also suggest greater risk levels among patients with SCZ compared to BD . Other studies report mixed findings, including similar rates of MetS and greater prevalence of smoking and central adiposity in SCZ, but lower levels of TC and LDL‐C .…”
Section: Discussionmentioning
confidence: 99%
“…influenced by fewer confounding ‘environmental factors’). In a real clinical setting, the major and defining problem of the patients with SCZ and BD is obesity (Manu et al 2015 ; Strassnig et al 2017 ). Therefore, we speculate, on the basis of our current results, that obesity in SCZ or BD may not be attributable entirely to genetic factors but might be greatly influenced by several environmental factors, such as medications (e.g.…”
Section: Discussionmentioning
confidence: 99%